Grinding Mills: How to Accurately Predict Their Power Draw (International Mineral Processing Congress, 2003)
"The first 90 years of the last century generated a considerable volume of technical literature on the subject of grinding mill power and its prediction. It is therefore surprising that during this time there were no published models for predicting grinding mill power draw which were validated using a wide range of comprehensive industrial scale data.Notwithstanding this lack of data, the majority of models placed limited emphasis on the internal dynamics of mills and relied on simple assumptions which considered the charge to take up a fixed position and shape.Laboratory based studies (Liddell, 1986), and industrial data (Morrell, 1993), showed that these assumptions did not hold over a wide range of operating conditions, and brought into doubt the ability of the (then) existing models to accurately predict grinding mill power draw. Furthermore no model treated AG,SAG and ball mills as a single class of devices whose power draw could be predicted with the same equations.Through a detailed investigation of the charge dynamics, coupled with a large data base of industrial mill power draws, this situation was rectified by the end of the century, by which time a model had been developed and validated, which accurately predicted the power draw of all wet tumbling mills. This paper describes this model and reviews some of the earlier attempts at mill power modelling."